Statues in Roman society : representation and response - Stewart, Peter, 1971- (Oxford studies in ancient culture and representation., 2003)
Statues were everywhere in the Roman world. They served as objects of cult, honours to emperors and noblemen, and memorials to the dead. Combining close attention to individual Roman texts and images with an unprecedented broad perspective on this remarkable phenomenon, Statues in Roman Society explains the impact which all kinds of statuary had on the ancient population.